Suicides and Suicidal Ideation During the Perinatal Period: Clinical and Demographic Data - Bazoukis, Xenophon; Eskitzis, Panagiotis; OROVOU, EIRINI; Arampatzi, Christiana; Spyropoulou, Areti (International Journal of Innovative Research in Medical Science, 2022)
Suicide is the second-leading cause of death for women in the postpartum period. Psychiatric disorders are common in pregnancy, affecting 15-29% of pregnant women, whereas clinical depression affects 10%-15% of them. Women during pregnancy and the postpartum period are particularly vulnerable to suicidal ideation. The prevalence of suicidal ideation ranges from 5% to 14% worldwide, while the rate of suicide during pregnancy and the postpartum period lies between two to three per 100,000 for countries like the UK and the USA. The main risk factor for suicidal ideation in the perinatal period is depression. Other mental illnesses, like schizophrenia, anxiety, bipolar and adjustment disorder, consist of risk factors too. Some of the high-risk social characteristics for suicide thoughts are younger age, unpartnered status and well-being with their marriage, high parity, non-Caucasian race, no health insurance, poor social support, unplanned pregnancy, low-income origin country, unemployment, low educational level and smoking. Obstetrics complications like severe vaginal laceration, low weight infants and admission in the neonatal intensive care unit, perinatal fetal mortality and prior abortions consist of risk factors. Physical, psychological or sexual intimate partner violence, sexual trauma and history of physical or sexual abuse in the army, physical or sexual abuse during childhood, all contribute to suicidal thought. Knowledge of the psychiatric history from the time of enrolment in maternity units, better identification of mental health problems via psychometric screening tools, as well as the use of proper referral and medication, should be the routine in health care services.